ROLE OF ANTIOXIDENTS ACCUMULATION AND PHOTOSYNTHETIC STABILITY FOR SUSTAINABLE COTTON PRODUCTION AND FIBRE QUALITY UNDER WATER STRESS CONDITIONS - YOUSAF , MI; GHANI , A; ZUBAIR , M; TALIB , I; KAUSAR , S; AKHTAR , I; MURTAZA , G; REHMAN , S; BUKHARI , MSJ; NAZAR , S; QAMAR , MJ; AKRAM , F; et al. (Biological and Clinical Sciences Research Journal, 2024)
One of the significant steps in developing water stress-tolerant, climate-smart cotton genotypes is evaluating and screening available cultivated germplasm. The current study was designed to evaluate the elite cotton strains developed for release in drought-prone areas of Punjab and Pakistan. Twenty-four cotton strains, along with two check varieties BH-184 and FH-142 were sown under RCBD in triplicates. The plant-to-plant and row-to-row distances were maintained at 30 cm and 70 cm, respectively. The recommended dosage of fertilizers N-P-K @ 100-36-37 kgs per acre was applied to all the treatments in all replications. The results revealed the presence of highly significant variations among cotton strains for studied plant parameters in twenty-four cotton strains. Correlation analysis unveiled the presence of highly significant and positive correlation of seed cotton yield with nodes per plant (r = 0.988**), sympodia per plant (r = 0.987**), transpiration rate (r = 0.983**), flavonoids (r = 0.982**), net photosynthetic rate (r = 0.979**), peroxidases (r = 0.968**), superoxide dismutase (r = 0.968**), bolls per plant (r = 0.914**), plant height (r = 0.885**), monopodia per plant (r = 0.725**) and ginning out turn (r = 0.430**) while the significantly negative correlation with CLCuV occurrence percentage (r = -0.526**). Cluster, principal component, and biplot analysis classify cotton strains into groups based on their performance under water-stress conditions. The results from PC1/PC2 biplot also verified the results obtained through correlations and further revealed that transpiration rate, net photosynthetic rate, peroxidases, superoxide dismutase, plant height, flavonoids, sympodia per plant, and superoxide dismutase were the most divergent traits and must be considered in developing a scheme to develop heat-tolerant cotton genotypes.